Photocatalyzed cycloaromatization of vinylsilanes with arylsulfonylazides - Fengjuan Chen (Nature Portfolio, 2021)
Arene-fused siloles have attracted interest due to their promising applications in electronic and optoelectronic devices. Here, the authors report Ir(III)-catalyzed cycloaromatization of ortho-alkynylaryl vinylsilanes with arylsulfonyl azides via α-silyl radical Smiles rearrangement for accessing naphthyl-fused benzosiloles under visible-light photoredox conditions.